If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11c + 47 + 21m + 88(x) = 19b Reorder the terms: 47 + 11c + 21m + 88x = 19b Solving 47 + 11c + 21m + 88x = 19b Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-47' to each side of the equation. 47 + 11c + 21m + -47 + 88x = -47 + 19b Reorder the terms: 47 + -47 + 11c + 21m + 88x = -47 + 19b Combine like terms: 47 + -47 = 0 0 + 11c + 21m + 88x = -47 + 19b 11c + 21m + 88x = -47 + 19b Add '-21m' to each side of the equation. 11c + 21m + -21m + 88x = -47 + 19b + -21m Combine like terms: 21m + -21m = 0 11c + 0 + 88x = -47 + 19b + -21m 11c + 88x = -47 + 19b + -21m Add '-88x' to each side of the equation. 11c + 88x + -88x = -47 + 19b + -21m + -88x Combine like terms: 88x + -88x = 0 11c + 0 = -47 + 19b + -21m + -88x 11c = -47 + 19b + -21m + -88x Divide each side by '11'. c = -4.272727273 + 1.727272727b + -1.909090909m + -8x Simplifying c = -4.272727273 + 1.727272727b + -1.909090909m + -8x
| 0.5x-8.3/2.2=5.5 | | -46+2x-71+8x= | | 0.50+7=15x+6 | | 7p+28q-70=0 | | -25+6x-46+2x= | | -z^2-4z+7=0 | | -46+2x+5x+48= | | 0.45t^2-2t+1=0 | | 5(x-3)+7=3x+2(-3+x) | | -s+6+3s=8s | | -20+z=4 | | 7b=11+95+41 | | -32-6x+8x-14= | | 1.126=2x+3 | | 2p+1=3p+7 | | -14x-39+5x+48= | | f(x)=3x^2+7x+1 | | -8y+7-5y=-18 | | 8x-14+5x+48= | | k^2+12k-14=0 | | -1/9n=17 | | 3(2+x)=4-(x+2) | | 7x+27=4x+12 | | -28=4h-3h | | X+(-7y)+(-4x)+8y= | | -20=4(8z-2) | | 2x+6y-8+19x=0 | | (2x-7)2=81 | | 5.5=0.5x-8.3/2.2 | | -3(4r-2)=-30 | | -18(x+1)+6(4x-5)=5(x-4)+8 | | 4X+y=8z |